Disparities in the treatment of cardiogenic shock: does sex matter?. (22nd November 2022) - Wang, Amy S; Nemeth, Samantha; Vinogradsky, Alice; Kurlansky, Paul; Brodie, Daniel; Fried, Justin; Takeda, Koji
Abstract: OBJECTIVES: The use of extracorporeal life support for cardiogenic shock has significantly increased over the past decade. However, there are insufficient data for the presence of sex-associated outcomes differences. Our study assesses differences between male and female patients placed on venoarterial extracorporeal life support (VA-ECLS) for cardiogenic shock from an international database. METHODS: This is a multicentre, retrospective study on 9888 adult patients on VA-ECLS for cardiogenic shock from the Extracorporeal Life Support Organization registry from 2011 to 2019. The 1:1 nearest neighbour propensity score matching was performed. The primary end point was in-hospital mortality. Secondary end points include bleeding, infection and other complications. RESULTS: There were 6747 (68%) male patients and 3141 (32%) female patients. Male patients were more likely to have history of myocardial infarction, coronary artery disease, diabetes, chronic kidney disease and congestive heart failure. Female patients were more likely to be centrally cannulated. After propensity score matching, there was no difference seen in in-hospital mortality. In regards to complications, female patients were more likely to experience limb ischaemia, whereas males were more likely to receive renal replacement therapy and have longer hospital stays. Multivariable logistic regression confirmed sex was not independently associated with mortality. CONCLUSIONS: There was no difference in-hospital mortality between male and female patients receiving VA-ECLS for cardiogenic shock. Female patients were more likely to have limb ischaemia as a complication. Varying cannulation approaches for female patients should be further investigated. Abstract : Biological sex plays a key role in cardiovascular disease and its management.